Application of transparent microperforated panels to acrylic partitions for desktop use: A case study by prototyping. Issue 2 (10th July 2021) - Sakagami, Kimihiro; Kusaka, Midori; Okuzono, Takeshi; Kido, Shigeyuki; Yamaguchi, Daichi
Abstract : There are various measures currently in place to prevent the spread of coronavirus (COVID-19); however, in some cases, these can have an adverse effect on the acoustic environment in buildings. For example, transparent acrylic partitions are often used in eating establishments, meeting rooms, offices, etc., to prevent droplet infection. However, acrylic partitions are acoustically reflective; therefore, reflected sounds may cause acoustic problems such as difficulties in conversation or the leakage of conversation. In this study, we performed a prototyping of transparent acrylic partitions to which a microperforated panel (MPP) was applied for sound absorption while maintaining transparency. The proposed partition is a triple-leaf acrylic partition with a single acrylic sheet without holes between two MPP sheets, as including a hole-free panel is important to prevent possible droplet penetration. The sound absorption characteristics were investigated by measuring the sound absorption in a reverberation room. As the original prototype showed sound absorption characteristics with a gentle peak and low values due to the openings on the periphery, it was modified by closing the openings on the top and sides. The sound absorption performance was improved to some extent when the top and sides were closed, although there remains the possibility of further improvement. For this study, only the sound absorption characteristics were examined in the prototype experiments. The effects during actual use will be the subject of future study.